1995
DOI: 10.1002/j.1556-6676.1995.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive‐Behavioral Approach to Chronic Pain Management

Abstract: More than one third of Americans suffer from recurring or persistent pain. Because this condition can result in depression, social isolation, disruption of intimate relationships, and prolonged disability, chronic pain sufferers may seek counseling. This article provides counselors with an introduction to the role of psychosocial processes in the experience of pain and offers assessment and intervention recommendations based on a cognitive‐behavioral therapy approach to pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The evaluation results also might point to the potential for establishing more trust and encouraging the patients to take greater responsibility in their own rehabilitation. However, when evaluating such results, the supervisors also need to be sensitive to the fact that active participation might be a new experience for the participants and that they might be quite sceptical 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation results also might point to the potential for establishing more trust and encouraging the patients to take greater responsibility in their own rehabilitation. However, when evaluating such results, the supervisors also need to be sensitive to the fact that active participation might be a new experience for the participants and that they might be quite sceptical 2 …”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary and cross‐cultural research has identified chronic pain as a major health problem 1–4 . Despite advances in understanding of nociception, as well as surgical and pharmacological advances, satisfactory elimination of pain remains a challenge for health professionals 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT proved very useful in conjunction with oncological treatment (Moorey & Greer, 2002). Numerous studies proved that CBT helps to alleviate pain or reduce the mental components of various somatic complaints, such as pain (Grant & Haverkamp, 1995;Reid et al, 2003), breathlessness (Bredin et al, 1999), nausea andvomiting (cf. Cathcart, 2006).…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%
“…It aims to provide insight and orientation to clinicians about what kind of outcome they can expect if they choose to apply this model in their clinical practice. The model integrates the following modalities documented as effective in pain-management: cognitive-behavioral therapeutic models for chronic pain (Caudill 1995;Grant and Havercamp 1995;Osborne et al 2006), progressive relaxation (Hammond 1990;Shaw and Erlich 1987) combined with art therapy (Sandmaier 2000), sensory awareness (Selver 1999), and clinical hypnosis for chronic pain (Barber 1996;Hammond 1990;Erickson 1994;Erickson et al 1990;Erickson et al 1976; Rossi and Cheek 1988). The synthesis of the above-mentioned techniques for pain-management was based on the hypothesis that systematic, progressive exposure to a variety of painmanagement techniques in a supportive environment can yield to more and longer-lasting benefits than those achieved by exposure to a single pain-management technique.…”
Section: Introductionmentioning
confidence: 99%